Impact of Concussions on Postural Stability Performance Using the Head Shake-Sensory Organization Test - John D Heick; Abdulaziz Alkathiry (North American Sports Medicine Institute, 2024)
# Background A concussion is a traumatic brain injury that can result in vestibular and oculomotor dysfunctions. The Head Shake-Sensory Organization Test was developed from the original Sensory Organization Test to measure a subject's ability to maintain balance while moving their head. # Purpose The purpose of this study was to compare the performance of adults with no history of concussion to those with a history of concussion on the Head Shake-Sensory Organization Test to determine if long-standing balance deficits are present after concussion. # Study Design Cross-sectional study # Methods Subjects with a history of concussion and healthy normal controls completed the Dizziness Handicap Inventory, the Activities-Specific Balance Confidence Scale, the sensory organization test, the head shake SOT, and the Foam Head Shake-Sensory Organization test in a single testing session. Scores were analyzed for differences between the two groups. # Results Twenty-five participants (nine patients with history of concussion and 16 healthy controls; mean age, 21.08±4.10 years) completed testing. The equilibrium scores in both groups significantly decreased with more complex tasks. Furthermore, the concussion group had significantly worse equilibrium scores than the control group during the Head Shake (p = 0.007) and Foam Head Shake-Sensory Organization Test (p = 0.002) tasks but not during the Sensory Organization Test task. # Conclusion Adding head shake and foam cushion conditions to postural stability tests improves sensitivity in detecting balance deficits in individuals with a concussion. # Level of Evidence 3